Experiences with a universal mindfulness and well-being programme at a UK medical school. Issue 4 (4th June 2018) - Stewart-Brown, Sarah; Cader, Mizaya; Walker, Thomas; Janjua, Sabah; Hanson, Emma; Chilton, Anne-Marie
Abstract : Purpose: The purpose of this paper is to examine the evaluation of a universal, mental well-being and mindfulness programme in a UK graduate entry medical school. Design/methodology/approach: Mixed methods used in the paper were the measurement of mental well-being and mindfulness in two cohorts at three time points over 15 months; descriptive, regression and repeated measures analysis with post hoc pairwise comparisons; qualitative interviews with purposive sample of 13 students after one year analysed thematically; and spontaneous anonymous feedback on the course. Findings: The course was a surprise to students, and reactions were mixed. Respect for its contents grew over the first year. Most students had actively implemented a well-being strategy by the end of the course, and an estimated quarter was practicing some mindful activity. In the context of an overall decline in well-being and limited engagement with mindfulness practice, increases in mindfulness were protective against this decline in both cohorts ( p <001). A small minority of students thought that the course was a waste of time. Their attitudes influenced engagement by their peers. The mindfulness and well-being practices of the facilitators were evident to students and influenced perceived effects. Research limitations/implications: The uncontrolled nature of this observational study and low response rates to the survey limit conclusions. Further research in other medical education settings is needed. Practical implications: Results are encouraging, suggesting modest benefit in terms of changing attitudes and practices and a modest protective effect on the well-being of students who engaged. Originality/value: This is the first study of a universal well-being and mindfulness programme in a UK medical school. Universal programmes are rare and evaluation studies are scarce.